(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article examines the role of emotional expression in political speech, exploring both the verbal and non-verbal techniques employed by political leaders and orators to convey their emotions and connect with their audience. The study delves into the strategic use of linguistic features, tone, and body language to elicit specific emotional responses and shape the narrative of political discourse. By analyzing a range of political speeches and presentations, the article provides insights into the sophisticated interplay between emotion and rhetoric in the realm of politics.